2017
DOI: 10.1038/npp.2017.220
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Blood Transcriptome Mega-Analysis: Shared Inflammatory Pathways across Biological Sex and Modes of Trauma

Abstract: Transcriptome-wide screens of peripheral blood during the onset and development of posttraumatic stress disorder (PTSD) indicate widespread immune dysregulation. However, little is known as to whether biological sex and the type of traumatic event influence shared or distinct biological pathways in PTSD. We performed a combined analysis of five independent PTSD blood transcriptome studies covering seven types of trauma in 229 PTSD and 311 comparison individuals to synthesize the extant data. Analyses by trauma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(92 citation statements)
references
References 45 publications
(45 reference statements)
6
85
0
1
Order By: Relevance
“…NUB1 was an even better predictor of stress state by gender in females (AUC 74%, p = 0.004) and by gender and diagnosis in female bipolars (AUC 78%, p = 0.02). NUB1, which was increased in expression in High Stress states in our studies, has previous convergent evidence for increase in expression in stress, in human brain in individuals exposed to social isolation before dying [10] and in blood in individuals exposed to combat traumas, as reported by Breen et al [11]. It also has evidence for increase in expression in the brain of mice subjected to chronic variable stress by Nestler and colleagues [12].…”
Section: Step 4: Testing For Diagnosticssupporting
confidence: 87%
See 1 more Smart Citation
“…NUB1 was an even better predictor of stress state by gender in females (AUC 74%, p = 0.004) and by gender and diagnosis in female bipolars (AUC 78%, p = 0.02). NUB1, which was increased in expression in High Stress states in our studies, has previous convergent evidence for increase in expression in stress, in human brain in individuals exposed to social isolation before dying [10] and in blood in individuals exposed to combat traumas, as reported by Breen et al [11]. It also has evidence for increase in expression in the brain of mice subjected to chronic variable stress by Nestler and colleagues [12].…”
Section: Step 4: Testing For Diagnosticssupporting
confidence: 87%
“…LAIR1, a decreased in expression biomarker, survived discovery, prioritization, and validation. It has previous convergent evidence from human studies of being decreased in expression in blood in PTSD related to childhood trauma [45] and to interpersonal trauma in females [11]. It is a strong predictor of state stress in females and of trait stress across all and in males.…”
Section: Step 7: Convergent Functional Evidencementioning
confidence: 84%
“…As the evidence for an association between PTSD and inflammation derives primarily from studies on blood inflammatory markers, we focus on findings from these studies in this section. At the outset, however, it may be worth noting that besides these targeted investigations into inflammatory markers, hypothesis‐free genome‐wide, blood DNA methylome, and blood transcriptome studies have identified immune/inflammatory‐related genes and pathways as the most dysregulated in patients with PTSD compared to controls.…”
Section: Inflammation and Ptsdmentioning
confidence: 99%
“…Notably, both studies identified a possible different involvement cell types in MDD between sexes. In addition to brain studies, genome-wide transcriptomic studies in peripheral blood samples of PTSD patients, such as by Breen et al, 86 have identified an analogous pattern of opposite gene expression changes between sexes and a possible involvement of different cell types. 87 Taken together, the high-throughput studies presented so far suggest that the male and female brains respond to stress in a different and regionspecific way.…”
Section: High-throughput Studiesmentioning
confidence: 99%